Comparison of Islamic Education Curriculum Evaluation In 2013 Curriculum and Independent Curriculum School and Madrasah - Nilawati Nilawati; Meidia Putri; Deti Susmita; Ahmad Lahmi; Rosniati Hakim (Prodi Pendidikan Keagamaan Islam, 2026)
Curriculum evaluation is an important component in ensuring the achievement of Islamic Religious Education (IRE) learning objectives in schools and madrasahs. The transition from the 2013 Curriculum to the Merdeka Curriculum has brought fundamental changes in the learning evaluation paradigm, in terms of approach, instruments, and the roles of teachers and students. This article aims to comparatively analyze the evaluation of the 2013 Curriculum and the Merdeka Curriculum in the context of Islamic Religious Education learning in schools and madrasas, highlighting aspects of the concept of evaluation, assessment approaches, implementation in the field, challenges faced, and its application to PAI learning. The research method used is a literature review. Data were obtained from various literature sources in the form of books and national and international journal articles relevant to curriculum evaluation, the 2013 Curriculum, the Merdeka Curriculum, and Islamic Religious Education. The analysis was conducted thematically and comparatively to identify similarities, differences, and evaluation trends in both curricula. The results of the study show that the evaluation of the 2013 Curriculum is more structured and oriented towards achieving Core Competencies and Basic Competencies through the assessment of attitudes, knowledge, and skills. Meanwhile, the Merdeka Curriculum emphasizes flexible, contextual, and student-centered evaluation through diagnostic and formative assessments. Overall, the Merdeka Curriculum is considered more adaptive in supporting meaningful PAI learning, although it still requires improvements in teacher readiness and educational system support.